Le guide Québec inc. 1997. Profil des 500 plus grandes entreprises au Québec - Laberge, Yves (Relations industrielles / Industrial Relations, 1999)
The article reviews the book, "Le guide Québec inc. 1997. Profil des 500 plus grandes entreprises au Québec," by Jean Auclair, Pierre Auger and Raymond Boisvert.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Corporations; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z